Covid-19 and Public Expenditure in Uganda: A Case of Ministry of Finance, Planning and Economic Development - Romano Stanely Tego (Uganda Christian University, 2026)
The study examined the impact of COVID-19 on public expenditure in Uganda: a case of the Ministry of Finance, Planning and Economic Development (MoFPED). It specifically focused on;establishing the influence of health crisis severity on public expenditure in Uganda, determining the effect of economic disruptions on public expenditure in Uganda, and examining the influence of government response measures on public expenditure in Uganda.The study was carried out using a cross sectional survey research design where both quantitative and qualitative research approaches were also used. The data was collected using questionnaires and interviews during the data collection, both purposive and simple random sampling methods were used. A sample size of 133 respondents who are the lower-level employees plus 10 top management of MoFPED was used in the study. The study findings revealed that COVID-19 had a significant positive impact on public expenditure in Uganda, particularly within the Ministry of Finance, Planning and Economic Development. The severity of the health crisis increased health sector funding and required budget reallocations (r = 0.535**, p < 0.01), while economic disruptions such as reduced revenue and trade declines prompted higher spending on stimulus and social protection programs (r = 0.672**,p < 0.01). Additionally, government response measures including lockdowns, emergency interventions, and sector-specific support further elevated public expenditure and influenced budget allocation priorities (r = 0.572**, p < 0.01). Lastly, the study recommended the need for MoFPED to strengthen health crisis contingency planning, enhance fiscal flexibility and adaptive budgeting, promote targeted and well-coordinated government interventions, deepen collaboration with development partners and international financial institutions, and institutionalize robust monitoring and evaluation systems to ensure transparency, accountability, and efficient public expenditure management during future emergencies.
Undergraduate Research